Effects of deficient mismatch repair on the prognosis of patients with stage II and stage III colon cancer during different postoperative periods - Chunze Zhang; Yixiang Zhan; Kemin Ni; Zhaoce Liu; Ran Xin; Qiurong Han; Guoxun Li; Hangyu Ping; Yaohong Liu; Xuanzhu Zhao; Wanting Wang; Suying Yan; et al. (BMC Cancer, 2022)
Abstract Background We evaluated the prognostic role of deficient mismatch repair (dMMR) systems in stage II and stage III colon cancer patients during different postoperative periods. We also assessed whether patients aged ≥75 could benefit from chemotherapy. Methods This retrospective study was conducted across three medical centers in China. Kaplan–Meier survival methods and Cox proportional hazards models were used to evaluate the differences in overall survival (OS) and disease-free survival (DFS) rates. Propensity score matching was performed to reduce imbalances in the baseline characteristics of the patients. Landmark analysis was performed to evaluate the role of dMMR during different postoperative periods. Results The median follow-up time for all patients was 45.0 months (25–75 IQR: 38.0–82.5). There was no significant OS (p = 0.350) or DFS (p = 0.752) benefit associated with dMMR for stage II and III patients during the first postoperative year. However, significant OS (p < 0.001) and DFS (p < 0.001) benefits were observed from the second postoperative year until the end of follow-up. These differences remained after propensity score matching. Moreover, chemotherapy produced no OS (HR = 0.761, 95% CI: 0.43–1.34, p = 0.341) or DFS (HR = 0.98, 95% CI: 0.51–1.88, p = 0.961) benefit for patients aged ≥75 years. Conclusion The benefits of dMMR in stage III patients were observed from the second postoperative year until the end of follow-up. However, the prognosis of patients with dMMR is not different from that of patients with proficient mismatch repair (pMMR) during the first postoperative year. In addition, elderly patients aged ≥75 years obtained no significant survival benefits from postoperative chemotherapy.